2006
DOI: 10.2503/jjshs.75.372
|View full text |Cite
|
Sign up to set email alerts
|

Self- and Cross-incompatibility of Various Citrus Accessions

Abstract: Self-incompatibility and compatibility of 65 citrus accessions were determined by pollen tube growth in the style. Lemon was self-compatible whereas the six pummelos and seven out of 11 its relatives were self-incompatible. Furthermore, among sour oranges and their relatives, two out of six accessions were, likewise, self-incompatible as were one out of five sweet orange and their relatives. Every yuzu and its relatives, except hyuga-natsu, were self-compatible. Of the mandarin and its relatives, 14 out of 28 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 7 publications
4
46
0
1
Order By: Relevance
“…Generative cell division occurs by three days after pollination in compatible tubes, but only rarely in incompatible tubes in Citrus (Kahn and DeMason, 1988) and almost all own pollen tubes were arrested in the styles (Wakana et al, 2004;Yamamoto et al, 2006). In pistils of self-incompatible Citrus plants pollinated with their own pollen, no pollen tubes reached the ovaries (Kahn and DeMason, 1988;Ton and Krezdorn, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…Generative cell division occurs by three days after pollination in compatible tubes, but only rarely in incompatible tubes in Citrus (Kahn and DeMason, 1988) and almost all own pollen tubes were arrested in the styles (Wakana et al, 2004;Yamamoto et al, 2006). In pistils of self-incompatible Citrus plants pollinated with their own pollen, no pollen tubes reached the ovaries (Kahn and DeMason, 1988;Ton and Krezdorn, 1967).…”
Section: Introductionmentioning
confidence: 99%
“…The CAPS genotypes of #16 and 23 may have arisen from self-fertilized seedlings of sour orange. This is because sour orange is selfcompatible (Yamamoto et al, 2006) and seedling propagation has been common there.…”
Section: Discussionmentioning
confidence: 99%
“…These trees were grown in the orchard of Kyushu University, Fukuoka, Japan. Grapefruit and sweet orange are semi self-compatible (Soost, 1969;Yamamoto et al, 2006) and polyembryonic. Selfincompatibility and monoembryony in other cultivars and accessions are listed in Table 1.…”
Section: Plant Materialsmentioning
confidence: 99%
“…Soost (1969) also found that the genotype of self-compatible grapefruit was composed of self-fertility (S f ) and self-incompatibility (S n ) alleles, since F 1 seedlings obtained by several crosses with grapefruit segregated into self-compatible and self-incompatible seedlings. Vardi et al (2000) and Yamamoto et al (2006) also found on the basis of segregation of selfincompatible hybrid seedlings that the genotypes of satsuma mandarin and sweet orange were S f S n . For a considerably long time after the work of Soost (1969), there was nothing but a few reports on the genotyping of Citrus cultivars for the S gene (Kim et al, 2010;Ngo et al, 2010b;Wakana et al, 1998), probably because of the existence of several barriers, such as male and/or female sterility, nucellar embryony, and a very long juvenile phase in zygotic seedlings for five to more than ten years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation